AB0246 FACTORS ASSOCIATED WITH THE TIME OF PRESENTATION OF CARDIOVASCULAR EVENTS IN A COHORT OF COLOMBIAN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Herrera, S.; Diaz-Coronado, J. C.; Rojas-Gualdrón, D.; Betancur-Vasquez, L.; Gonzalez-Hurtado, D.; Gonzalez-Arango, J.; Uribe-Arango, L.; Saavedra Chacón, M. F.; Lacouture-Fierro, J.; Monsalve, S.; Guerra-Zarama, S.; Serna, J. D.; et al.
Abstract : Background: Systemic lupus erythematosus is a systemic disease characterized by a compromise of vital organs. The autoimmune activity has been linked to accelerated endothelial damage and increased cardiovascular risk and its outcomes such as heart attack, stroke, and peripheral arterial disease(1). Patients with Lupic nephritis have been characterized by requiring aggressive immunosuppressive therapies apart from prolonged and progressive use of corticosteroids, what you have shown can accelerate these outcomes(2). Other factors such as secondary arterial hypertension, dyslipidemia among others are factors to consider (3). Objectives: To analyze clinical and immunological characteristics associated with time to severe renal involvement in patients with Systemic Lupus Erythematous in a Colombian cohort followed for one year, between January 2015 and December 2018. Methods: Retrospective follow-up study based on clinical records of patients with SLE diagnosis that fulfilled either 1987 American College of Rheumatology Classification Criteria for SLE or 2011 Systemic Lupus International Collaborating Clinics (SLICC) classification criteria for SLE. Patients with cardiovascular disease outcomes such as angina, acute myocardial infarction, stroke, transient cerebral ischemia and chronic arterial occlusive disease were included. Patients who did not have at least two follow-up measurements or had structural heart disease, valvulopathies, arrhythmias, myocarditis, pericarditis were excluded. The main outcome was defined as the time from diagnosis to cardiovascular diseases. Clinical and immunological characteristics were analyzed. Descriptive statistical analyses of participant data during the first evaluation are reported as frequencies and percentages for categorical variables, and as medians and interquartile ranges for quantitative variables. Age and sex adjusted survival functions and Hazard Ratios (HR) with 95% confidence intervals and p-values were estimated using parametric Weibull models for interval-censored data. P values < 0.05 were considered statistically significant Results: 547 patients were analyzed: 29 were left-censored as they presented renal involvement at entry, 22 were interval censored as outcome occurred between study visits, and 496 were right-censored as involvement was not registered during follow-up. 528 (96.5%) patients were female, median age at entry was 46 (IQR = 23) and median age to diagnosis was 29.4 (IQR = 20.9). Statistically significant age and sex adjusted variables were High Blood Pressure (HBP) HR = 2.0 (95%CI 1.1-3.6; p-value <0.018) and cumulative prednisolone dose (>10 gr vs <2 gr) HR = 2.4 (95%CI 1. 1-5.1; p-value = 0.023). Figure 1 shows the age and sex adjusted survival function for HBP Conclusion: HBP and cumulative steroid doses accelerate the onset of cardiovascular diseases in patients with lupus more than two times. Maintaining blood pressure in goals and performing early clearance of glucocorticoids could improve outcomes in these patients who are already considered a high cardiovascular risk References: [1]Hans-Joachim Anders, Ramesh Saxena, Ming-Hui Zhao. Lupus Nephritis. Nat Rev Dis Primers. 2020 Jan 23;6(1):7. [2]Shanthini Kasturi, Lisa R Sammaritano. Corticosteroids in Lupus. Rheum Dis Clin North Am, 42 (1), 47-62, viii [3]César Magro-Checa, Juan Salvatierra, José Luis Rosales-Alexander, et al. Cardiovascular risk in systemic lupus erythematosus: implicated factors and assessment methods. Semin Fund Esp Reumatol. 2012;13(3):95–102 Disclosure of Interests: Sebastian Herrera Speakers bureau: academic conference, Juan camilo Diaz-Coronado: None declared, Diego Rojas-Gualdrón: None declared, Laura Betancur-Vasquez: None declared, Daniel Gonzalez-Hurtado: None declared, Juanita Gonzalez-Arango: None declared, laura Uribe-Arango: None declared, Maria Fernanda Saavedra Chacón: None declared, Jorge Lacouture-Fierro: None declared, Santiago Monsalve: None declared, Sebastian Guerra-Zarama: None declared, Juan david Serna: None declared, Julian Barbosa: None declared, Deicy Hernandez-Parra: None declared, Ana Sierra: None declared, Ricardo Pineda.Tamayo: None declared